Both Group 4 Capsule and Lipopolysaccharide O-Antigen Contribute to Enteropathogenic Escherichia coli Resistance to Human α-Defensin 5 - Thomassin, Jenny-Lee (Public Library of Science, 2013)
Enteropathogenic and enterohemorrhagic Escherichia coli (EPEC and EHEC) are food-borne pathogens that colonize the small intestine and colon, respectively. To cause disease, these pathogens must overcome the action of different host antimicrobial peptides (AMPs) secreted into these distinct niches. We have shown previously that EHEC expresses high levels of the OmpT protease to inactivate the human cathelicidin LL-37, an AMP present in the colon. In this study, we investigate the mechanisms used by EPEC to resist human α-defensin 5 (HD-5), the most abundant AMP in the small intestine. Quantitative PCR was used to measure transcript levels of various EPEC surface structures. High transcript levels of gfcA, a gene required for group 4 capsule (G4C) production, were observed in EPEC, but not in EHEC. The unencapsulated EPEC ∆gfcA and EHEC wild-type strains were more susceptible to HD-5 than EPEC wild-type. Since the G4C is composed of the same sugar repeats as the lipopolysaccharide O-antigen, an -antigen ligase (waaL) deletion mutant was generated in EPEC to assess its role in HD-5 resistance. The ∆waaL EPEC strain was more susceptible to HD-5 than both the wild-type and ∆gfcA strains. The ∆gfcA∆waaL EPEC strain was not significantly more susceptible to HD-5 than the ∆waaL strain, suggesting that the absence of -antigen influences G4C formation. To determine whether the G4C and -antigen interact with HD-5, total polysaccharide was purified from wild-type EPEC and added to the ∆gfcA∆waaL strain in the presence of HD-5. The addition of exogenous polysaccharide protected the susceptible strain against HD-5 killing in a dose-dependent manner, suggesting that HD-5 binds to the polysaccharides present on the surface of EPEC. Altogether, these findings indicate that EPEC relies on both the G4C and the -antigen to resist the bactericidal activity of HD-5.